Strategi Nilai Berita Kegiatan Vaksinasi Covid-19 Untuk Media Massa di Institut Ilmu Sosial dan Manajemen Stiami - Heru Sudinta; Ecep Suwardani Yasa; Iwan Irwansyah (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2022)
In order to maximize the prevention of the spread of the COVID-19 virus, the Government seeks to maximize and meet the target of the accelerated vaccination program. Mass vaccination is being intensified to make it easier for the public to access Covid-19 vaccination health services. However, this government activity program requires the support of adequate locations and facilities which include the availability of space and human resources. Universities are considered to be adequate facilities to accommodate government programs for Covid-19 vaccination activities. As one of the leading private universities in Bekasi City, the STIAMI Institute took part in the success of the government program. The university, which has a central campus in Jakarta, assessed that the Covid-19 Mass Vaccination activity could be collaborated with Community Service (PKM) activities. Community Service Activities are the obligations of Lecturers listed in the Tridharma of Higher Education. Utilizing the media relations network, the STIAMI Institute seeks to determine the value of news and package Covid-19 mass vaccination activities as an optimal publicity medium in marketing communications. Public Relations strategy by combining media relations and marketing communications is able to generate publicity ideas. The news value chosen to be an attraction for mass media coverage is "Dare to Vaccine Get a College Scholarship". The incessant publicity carried out by the STIAMI Institute is expected to be able to maintain its image and reputation in the eyes of the public, both potential customers, consumers, competitors and internal institutions.